El crowdfunding llegó al Perú, ¿para quedarse? - Mercado Espinosa, Ricardo (2021)
This article seeks to briefly describe the phenomenon of crowdfunding or participatory financing as an alternative financing mechanism for entrepreneurs who, for the most part, have barriers to access to funding in the traditional financial system. It also aims show the main challenges that actors of crowdfunding have so that this mechanism stays in time and helps the development of Peruvian Economy.